1992
DOI: 10.1161/01.atv.12.7.780
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma fibrinogen: relation to body weight, waist-to-hip ratio, smoking, alcohol, age, and sex. Results from the second MONICA Augsburg survey 1989-1990.

Abstract: In the second World Health Organization MONItoring Trends and Determinants in CArdiovascular Disease (MONICA) Augsburg survey in 1989-1990 (#1=4,940), the association between nephelometric plasma fibrinogen level and lifestyle-related potential determinants was assessed in 4,434 subjects aged 25-74 years (89.8% of participants). Irrespective of pregnancy and the use of oral contraceptives, crude fibrinogen values were consistently higher in women than in men of all ages (age-standardized difference, 12.2 mg/dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
88
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(109 citation statements)
references
References 37 publications
18
88
1
2
Order By: Relevance
“…tional studies including high alcohol drinkers suggested a U-shaped curve for the association of alcohol consumption and fibrinogen, particularly among men, with the minimum of the curve ranging between 20 to 60 g alcohol/day (Krobot et al, 1992;Mennen et al, 1999;Mukamal et al, 2001). In this study, no relation between alcohol consumption and antithrombin III was found, while results of other studies remained inconclusive (Kiechl et al, 1996;Mezzano et al, 2001).…”
Section: Alcohol and Risk Factors Of Cardiovascular Disease M Burger contrasting
confidence: 54%
“…tional studies including high alcohol drinkers suggested a U-shaped curve for the association of alcohol consumption and fibrinogen, particularly among men, with the minimum of the curve ranging between 20 to 60 g alcohol/day (Krobot et al, 1992;Mennen et al, 1999;Mukamal et al, 2001). In this study, no relation between alcohol consumption and antithrombin III was found, while results of other studies remained inconclusive (Kiechl et al, 1996;Mezzano et al, 2001).…”
Section: Alcohol and Risk Factors Of Cardiovascular Disease M Burger contrasting
confidence: 54%
“…It has been suggested that the favorable association between plasma fibrinogen levels and regular exercise are likely due, at least in part, to lower body fatness. 28,29 Indeed, in the present study, percent body fat was the primary determinant of plasma fibrinogen level, accounting for approximately one third of the variability.…”
Section: Fibrinogensupporting
confidence: 44%
“…[40][41][42][43][44] Our study found that 19% to 29% of the variance in plasma fibrinogen concentration could be explained by age and anthropometric, lifestyle, and metabolic factors. The extent to which genetic factors determine the concentration of plasma fibrinogen is not entirely known.…”
Section: Discussionmentioning
confidence: 99%